Transforming the Authority of the Archive Undergraduate Pedagogy and Critical Digital Archives - Gustavson, Andi; Nunes, Charlotte (Lever Press, 2023)
Featuring a wide array of perspectives, Transforming the Authority of the Archive details new roles for archives in undergraduate pedagogy and new roles for undergraduates in archives. While there has long been a place for archival exploration in undergraduate education (especially primary source analysis of items curated by archivists and educators), the models offered here engage students not only in analyzing collections, but also in the manifold challenges of building, stewarding, and communicating about collections. In transforming what archives are to undergraduate education, the projects detailed in this book transform the authority of the archive, as students and community partners claim powers to curate and create history. Contributions to this volume represent a range of institutions including small liberal arts colleges, HBCUs, Ivy Leagues, large research institutions, and community-based collections. The assignments, projects, and initiatives described across this volume are fundamentally concerned with the challenge to model digital archival collections so as to center individual and community voices that are historically under-engaged in the archives. To address this challenge, contributors describe various approaches to substantively, often radically, redistribute archival resources and authority. The chapters within Transforming the Authority of the Archive offer thoughtful and creative pedagogical approaches to counter the presumed neutrality of the archive and advocate a shared understanding of the contingency of archival collections. This book is a must-read for liberal arts faculty, graduate students, archivists (both community- and institutionally-affiliated), information-studies professionals, librarians, and other professionals working and teaching in archives, museums, libraries, and other cultural heritage institutions.